Bispectoral index scores of pediatric patients under dental treatment and recovery conditions: Study of children assigned for general anesthesia under propofol and isofloran regimes - Dana Tahririan; Naser Kaviani; Nosrat Nourbakhsh (Wolters Kluwer Medknow Publications, 2016)
Background: This study was planned to determine the relationship between bispectoral index (BIS) during dental treatment and recovery conditions in children undergoing two regimes of anesthesia of propofol and isoflurane. Materials and Methods: In this single-blind clinical trial study, 57 4-7-year-old healthy children who had been referred for dental treatment under general anesthesia between 60 and 90 min were selected by convenience sampling and assigned to two groups, after obtaining their parents' written consent. The anesthesia was induced by inhalation. For the first group, the anesthesia was preserved by a mixture of oxygen (50%), nitrous oxide (50%), and isoflurane (1%). For the second group, the anesthesia was preserved by a mixture of oxygen (50%), nitrous oxide (50%), and propofol was administered intravenously at a dose of 100 Ng/kg/min. The patients' vital signs, BIS, and agitation scores were recorded every 10 min. The data were analyzed by repeated measure ANOVA and t-tests at a significance level of α = 0.05 using SPSS version 20. Results: The results of independent t-test for anesthesia time showed no statistically significant difference between isoflurane and propofol (P = 0.87). Controlling age, the BIS difference between the two anesthetic agents was not significant (P > 0.05); however, it was negatively correlated with the duration of anesthesia and the discharge time (P = 0.001, r = -0.308) and (P < 0.001, r = -0.55). Conclusion: The same depth of anesthesia is produced by propofol and isoflurane, but lower recovery complications from anesthesia are observed with isoflurane.